اللغة العربية ولهجات القبائل المشهورة (الدراسة المقارنة بين لهجة قبيلة قريش، تميم، وأسد) - Fina Aunul Kafi (INAIFAS PRESS, 2019)
Arabic is famous for having several tribes. Each tribe has different dialect. Now the most famous leaves only three dialects, namely Quraysh, Tamim, and Asad. Many data reported that those dialects were not only different in terms of phonetics, but also other linguistic aspects. This study aimed to find the different dialect characteristics of the three popular dialects so that it could make it easier to understand the language that was generally used in Arab's community. The result showed that the three dialects most commonly used were Quraysh and Tamim dialects. In contrary, Asad’s dialect was only in small communities. All three dialects had differences in phonetic terms and sentences. This result indicates that phonetics and sentences of Quraysh dialect can be changed into other forms in Tamim and Asad dialects with several categories.